Uji Daya Hasil dan Seleksi Famili Padi Generasi F4 dan F6 Hasil Persilangan Sintanur x PTB 33 dan Pandanwangi x PTB 33 di Jatinangor: Uji Daya Hasil dan Seleksi Famili Padi Generasi F4 dan F6 Hasil Persilangan Sintanur x PTB 33 dan Pandanwangi x PTB 33 di Jatinangor - Zulfa Afifah; Nono Carsono; Santika Sari; Anas Anas (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
High yielding is one of main objectives on rice breeding. A preliminary yield trial is one of steps in the selection process of developing new varieties. Selection for yield and its component traits is a complex process due to the nature of quantitative traits. The right selection approach may improve the effectiveness of the selection. It is therefore the objective of the current study was to select high yielding rice genotypes. A total of 10 promising rice families were evaluated and compared to four check varieties. Least Significant Increase (LSI), and selection index (Mulamba & Mock and Genotype Ideotype Distance index) analysis were performed. LSI test showed that PP48-5 and SP101-3-1-5 had the best performance in almost all traits compared to the lowest average of the check variety. The selection index found that SP101-3-1-5 had highest yield selection index and was recognized as superior family by selection index. SP101-3-1-5 is selected as potential family to be developed as a new high yielding rice varieties